Exploring the Initiatives to Incorporate Immigrant Teachers into School Systems: A Scoping Review - Ferrada-Quezada, N (SAGE Publications Inc., 2024)
The objective of this study is to conduct a scoping review of the literature on access and permanence initiatives for the teaching profession aimed at immigrant teachers. The guidelines from the PRISMA-Scr protocol and the Johanna Briggs Institute protocol are used for this purpose. The literature search was performed in 8 databases, selecting 27 documents published between 2006 and 2021. The results show numerous studies on immigrant teachers, but many of them focused on their experiences after having passed an access and permanence initiative, while only a few described them. Three main initiatives for immigrant teachers were found: recertification, attraction, and professional development. Recertification initiatives are the most studied initiatives. No publications made in Ibero-American countries were found. There is a need to create partnerships and networks among researchers and policy makers to support countries that do not have initiatives for immigrant teachers. In addition to injecting resources for initiatives related to the retention and professional development of immigrant teachers, to avoid the loss of valuable human resources that are in short supply. © The Author(s) 2024.